Studi Linguistik : Penggunaan Multilingual pada Siswa Kelas V SD Negeri 058374 Sei Limbat - Wirda Hayatina Lubis; Biworo Frida Gurning; Elly Prihasti Wuriyani; Wisman Hadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Nowadays, children learn not only one language, but several languages. For example, at school, students use Indonesian, at home, they use their mother tongue, and there are other languages spoken in the community. Language learning at school is not limited to one language only, but also includes other languages. The purpose of this study is to understand why children today can communicate in multiple languages. Multilingual users are those who use multiple languages. A multilingual person is one who uses a wide variety of languages in daily life depending on the context and situation. This research uses descriptive-analytical method. The findings of this study show that many people today speak more than one language. This shows that the general public, particularly in Indonesia, and around the world, use languages as a means of communication. The use of multiple languages can affect the well-being of society. Sociolinguistics focuses on the relationship between language and society. The goal of sociolinguistics is to explain why people use different languages in different social contexts.